Mobile apps for teaching and learning English as a foreign language to a teenagers and adults - Strahm Voulquin, Emilio Willy; Canese, Valentina; Castillo Alvarenga, Mirtha Beatriz (Ñemitỹrã, 2020)
This study evaluated and reviewed phone apps designed to aid in the learning of English of English as a Foreign Language (EFL). From among ninety frequently-downloaded free Android apps, the authors selected and reviewed twelve apps for their potential use by teenagers and adults in EFL classrooms at the intermediate and advanced levels. They employed an author-developed rubric with eight criteria: curriculum connection, authenticity, feedback, differentiation, performance, sharing, user-friendly, and appeal. Findings suggest that several Android apps exist that can potentially enhance the teaching and learning of English. Implications suggest that if teachers are trained at reviewing apps, they can become empowered at selecting digital tools for making their lessons more compelling and student-centered. Yet, to maximize the efficacy of these apps in their EFL classrooms, teachers should provide support and feedback related to the skills being practiced by their students on these apps.